2021
DOI: 10.1002/jmri.28024
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Reconstruction Enables Highly Accelerated Biparametric MR Imaging of the Prostate

Abstract: Background Early diagnosis and treatment of prostate cancer (PCa) can be curative; however, prostate‐specific antigen is a suboptimal screening test for clinically significant PCa. While prostate magnetic resonance imaging (MRI) has demonstrated value for the diagnosis of PCa, the acquisition time is too long for a first‐line screening modality. Purpose To accelerate prostate MRI exams, utilizing a variational network (VN) for image reconstruction. Study Type Retrospective. Subjects One hundred and thirteen su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Initially, in prostate MRI, machine learning approaches have been applied mostly for lesion detection and classification [ 28 , 29 , 30 ]. However, recent studies also focused on scan acceleration in prostate MRI [ 18 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, in prostate MRI, machine learning approaches have been applied mostly for lesion detection and classification [ 28 , 29 , 30 ]. However, recent studies also focused on scan acceleration in prostate MRI [ 18 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the potential value of DL-based approaches for retrospectively accelerated MRI of the prostate MRI and the knee. [ 17 , 18 ] However, to study the clinical performance of any acceleration method, it is essential to investigate the effects of prospective undersampling on image quality. Interactions between the actual k-space sampling scheme and physiological motion or eddy currents related to pseudo-random sampling might impact the quality of the acquired k-space data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In the context of deep-learning, the soft-SENSE model has been used recently. [37][38][39] VarNet and MoDL only update the image corresponding to the first set of coil sensitivity maps in the network block. We use the MSE loss on the coil images since the coil images serve as a reference independent of the estimated coil sensitivity maps.…”
Section: Extensions To the Sense-modelmentioning
confidence: 99%
“…The soft-SENSE model is suitable if the object exceeds the FOV since one set of coil sensitivity maps can not explain infolding artifacts [33]. In the context of deeplearning, the soft-SENSE model has been used recently in [34,35]. BART's implementations of VarNet and MoDL only uses the image corresponding to the first set of coil sensitivity maps in the network part of the soft-SENSE model.…”
Section: Extensions To the Sense-modelmentioning
confidence: 99%